Evaluating the adaptive capacity of the giant panda in response to climate change since the last glacial maximum - Yadong Xu; Wen He; Xintian Yang; Yunqiu Li; Xiaoping Yu; Xinping Ye (Ecological Indicators)
Evaluating the adaptive capacity of species to past climate change is a crucial component in understanding how species respond to climatic shifts. This information serves as a vital foundation for guiding conservation practices under future environmental changes. We reconstructed the potential suitable habitat maps for giant pandas (Ailuropoda melanoleuca) during the Last Glacial Maximum (LGM, ∼22 ka) and mid-Holocene (MH, ∼6 ka) climates via an ensemble species distribution modelling approach, and compared them to the potential suitable habitats at current stage, we also estimated and compared the bioclimatic velocity of giant pandas to the climatic velocities since LGM. The results showed that the suitable habitat area for giant pandas has increased by 12.47 % from LGM to MH, and then decreased by 5.37 % from MH to current stage. The estimated climatic velocity over the suitable habitats for giant pandas was 16.00 ± 5.83 km·kyr−1 from LGM to MH and 46.13 ± 18.96 km·kyr−1 from MH to nowadays. The bioclimatic velocities for these two periods were 0.55 ± 0.55 km·kyr−1 and 8.47 ± 10.45 km·kyr−1, respectively. The result indicated that giant pandas have successfully adapted to the climate changes since LGM by migrating at a rate that lags behind the speed of climate change within their current distribution range. However, this does not imply that giant pandas possess sufficient migratory capabilities to cope with future climate crises, as the current rate of climate change exceeds that of any historical periods.